A variational scheme for hyperbolic obstacle problems. (November 2019) - Bonafini, M.; Novaga, M.; Orlandi, G.
Abstract: We consider an obstacle problem for (possibly non-local) wave equations, and we prove existence of weak solutions through a convex minimization approach based on a time discrete approximation scheme. We provide the corresponding numerical implementation and raise some open questions.